Productivity Analysis of Micro-Trenching Using Simphony Simulation Modeling - Hediyeh Vaseli; Leila Hashemian; Alireza Bayat (Civil Engineering Journal, 2020)
Micro-trenching is an innovative method for installing fiber optic cable in residential areas and business districts which minimizes surface scarring and potential negative social and environmental impacts. This method has three major steps including cutting a narrow trench in the pavement, cable installation and trench backfilling. This paper discusses a Simphony simulation model of the micro-trenching procedure and analyzes its productivity. Brief descriptions of the micro-trenching method and two field installations used to validate the model are included. A simulation model was developed for two different installation depths of 7.6 and 23 cm using two different methods. To provide an estimation of project duration, the impact of weather conditions on micro-trenching productivity was also considered. The developed model can be used for what if scenarios and for predicting the outcomes, which may be useful for studying the procedure and verifying if any productivity improvement can be achieved. The results indicate that the influence of installation depth is more significant than the impact of weather conditions. Reducing installation depth from 23 cm to 7.6 could improve productivity up to 50% while cold weather condition can reduce productivity by 18.8%. The simulation model demonstrates that the productivity can be improved up to 16% by overlapping two steps during the installation process: starting the cleaning procedure when a portion of cutting is completed. Doi: 10.28991/cej-2020-03091607 Full Text: PDF